DOP18 Brain structural correlates of fatigue in active and quiescent Crohn's Disease. (30th January 2023) - Thomann, A; Schmitgen, M; Szabo, K; Ebert, M; Reindl, W; Wolf, C
Abstract: Background: Fatigue is a common and debilitating symptom in IBD, affecting the majority of patients with active disease. While impaired energy metabolism may contribute to the development of fatigue during active phases of the disease, the high prevalence of fatigue in remitted IBD is less comprehensible. The underlying mechanisms of fatigue are poorly understood, but a disturbance along the microbiota-gut-brain-axis seems likely. This study examined brain structural correlates of fatigue in patients with Crohn's Disease (CD) in an active (aCD) or quiescent (qCD) state and healthy controls (HC). Methods: Patients with CD (n=45; aCD=22, qCD=23) and HC (n=35) underwent structural MRI at 3T and completed a questionnaire (WEIMuS) to assess somatic (sFat) and cognitive fatigue (cFat). Whole-brain grey matter volume (GMV) was analysed using CAT12 in SPM12. We calculated group differences between HC and CD as well as CD subgroups and extracted raw values of anatomical regions with significant differences between the groups (at p<.005; k=173) for subsequent correlation analyses with sFat and cFat (Spearman's ρ). Results: Patients had significantly higher mean fatigue scores than HC (both sFat and cFat, p<0.001). Patients with aCD had higher mean fatigue scores than qCD, but differences between groups were not significant (p>0.2). Differences in GMV between CD (aCD+qCD) and HC were detected in frontal, temporal, parietal, and occipital cortex, as well as in the putamen and cerebellum (all p<.005). Across the patient group, GMV in the majority of the above mentioned regions was negatively correlated with sFat and cFat (Fig. 1). Subgroup analysis revealed a negative correlation between sFat and GMV in inferior frontal gyrus in aCD, while several other regions were negatively associated with both sFat and cFat in qCD (all p<.05). No positive correlations between GMV and fatigue were observed. Conclusion: This study suggests a brain structural involvement in fatigue symptoms in CD. While fatigue is more common in active CD, the symptom correlation with GMV in this study was more widespread in patients with quiescent disease. The results indicate possible differences in the development and/or processing of fatigue in different disease states and may reflect disturbed brain-gut-interactions in quiescent CD with fatigue. These findings can help to increase our understanding of fatigue in CD and indicate that different therapeutic approaches targeting fatigue in CD may need to be considered depending on the state of disease activity.